PARTISIPASI ANAK MUDA MEMBANGUN RASA HORMAT, KEBANGGAAN DAN PERBEDAAN PADA KLUB TENIS LAPANGAN - Dwi Hartanto (Jurnal Pendidikan Olah Raga, 2023)
This research aims to find out how much the value of tennis club in Pontianak is in understanding conflict between members. The collection of data obtained through observation of members and interviews of each member. The number of participants or members used is 3 people selected based on their general level. This study uses ethnographic qualitative methods. The data obtained is collected as a tool to analyse the text. The results obtained from collecting data on members really participate in the club because of a great desire to grow the club, pride in the club and a model for forming new clubs.